PENGARUH PEMBERIAN AIR KELAPA MUDA TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI : STUDI LITERATURE - Wulandari, Putri; Syarifah, Anita; Awaluddin, Awaluddin (Ensiklopedia of Journal, 2025)
Hypertension or high blood pressure disease is a chronic condition characterized by increased blood pressure on the walls of arterial blood vessels. Hypertension is often referred to as The Silent Killer because usually the patient does not know that he has hypertension and is only known after complications occur. Hypertension can be controlled with non-pharmacological therapy, one of which is consuming young coconut water. Young coconut water contains high potassium which can lower blood pressure. Purpose : The purpose of this study was to determine the effect of young coconut water (cocos nucifera L) on lowering blood pressure in patients with hypertension. Method : The research method uses literature studies from research results published in 2015-2024. Literature search using keywords young coconut water, high blood pressure, and blood pressure. Using Google Schoolar data base with criteria that use article titles that discuss the effect of young coconut water on the blood pressure of hypertensive patients, the year of publication of the article at least the last 10 years. Result : The results of the analysis of 20 journals illustrate that there is an effect of consuming young coconut water (Cocos nucifera L) on lowering blood pressure in people with hypertension.Key Words : Blood Pressure, Hypertension, Young coconut water